Dextran Nanocapsules with ω-3 in Their Nucleus: An Innovative Nanosystem for Imiquimod Transdermal Delivery - Gisela F. Carreño; María Javiera Álvarez-Figueroa; José Vicente González-Aramundiz (MDPI AG, 2022)
Transdermal administration of molecules across the skin has gained interest because it can be considered a non-invasive route compared with traditional ones. However, going through the skin is challenging due to the presence of the stratum corneum, the main barrier of substances. For this reason, the goal of this research was the combination of omega-3 (ω-3) and a dextran sulfate assembly in a nanostructure form, which allows passage through the skin and improves the bioavailability and the therapeutic profiles of active molecules, such as imiquimod. Here we report a new colloidal system, named dextran nanocapsules, with ω-3 in its nucleus and a coat made of dextran sulfate with a size ~150 nm, monomodal distribution, and negative zeta potential (~−33 mV). This nanosystem encapsulates imiquimod with high efficacy (~86%) and can release it in a controlled fashion following Korsmeyer-Peppas kinetics. This formulation is stable under storage and physiological conditions. Furthermore, a freeze-dried product could be produced with different cryoprotectants and presents a good security profile in the HaCaT cell line. Ex vivo assays with newborn pig skin showed that dextran nanocapsules promote transdermal delivery and retention 10 times higher than non-encapsulated imiquimod. These promising results make this nanosystem an efficient vehicle for imiquimod transdermal delivery.